Virtual technologies in professional training of student-athletes: assessment of functional indicators and competencies - Shmakova A.P. ,; Belozerova L.A. ,; Soltis V.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study the functional indicators of the cardiovascular system and respiration of students with massive sports categories when passing a VR scenario for assessing competencies with an emotionally intense situation. Methods and structure of the study. The scientific experiment involved 30 students of the Faculty of Physical Culture and Sports of a pedagogical university with mass sports ranks. The control group consisted of 33 university students who did not regularly engage in sports. The subjects' heart rate, blood pressure, pulse pressure, Kerdo autonomic index, endurance coefficient, index of functional changes, type of self-regulation of blood circulation, respiratory rate, and Hildebrandt index were assessed in the subjects at rest, during instruction, and during the passage of the scenario using VR glasses. The study was carried out using the “Virtual pedagogical simulator Tut360”, containing emotionally intense pedagogical scenarios (“Fire at school”). At the same time, the formation of psychological and pedagogical competencies (UС-3, UС-8, GPC-3, GPC-4, GPC-6, PC-1) was automatically assessed. Results and conclusions. In the group of students systematically involved in sports, lower heart rate, blood pressure, Kerdo index, type of self-regulation of blood circulation and Hildebrandt index were found at all stages of the study compared to the control group. More pronounced changes in indicators of the cardiovascular and respiratory systems (not always significant) were detected in student-athletes at the stage of familiarization with the instructions, and in untrained students - at the stage of passing the scenario. Based on the results of completing the scenario, the development of psychological and pedagogical competencies among students of the two groups was noted to be approximately at the same level. We believe that the use of VR technologies in the process of professional training of students of various specialties will allow them to psychologically prepare for performing real professional tasks and increase the efficiency of the educational process.